Projections of Spanish Jesuit Scholasticism on British Thought
1 online resource
Keywords: Spanish Jesuits such as Francisco Suárez (1548–1617), José de Acosta (1540–1600), Pedro de Ribadeneira (1526-1611) and Juan de Mariana (1536-1624) had a powerful impact on English thinkers of the magnitude of John Locke (1632–1704), Francis Bacon (1561-1626), Robert Persons (1546-1610), Algernon Sidney (1623-1683), and, later, William Robertson (1721–1793), Thomas de Quincey (1785–1859) and Hilaire Belloc (1870–1953). An influence that was sometimes hidden and always controversial. This work highlights the importance of this influence regarding thought on politics, law and natural rights. A constitutionalist understanding of political power, the recognition and promotion of innate rights and the necessary subjection of rulers to the law, all form part of the important legacy of these scholastic doctors for European intellectual heritage. Contributors to this volume: Rafael Alé Ruiz, Francisco T. Baciero Ruiz, Francisco Castilla Urbano, José Luis Cendejas Bueno, Alfonso Díaz Vera, Francisco Javier Gómez Díez, Cecilia Font de Villanueva, León M. Gómez Rivas, Fermín del Pino Díaz, Leopoldo J. Prieto López, Daniel Schwartz, Lorena Velasco Guerrero, and María Idoya Zorroza Huarte.